Two new combinations in Brazilian Dendropanax (Araliaceae) - Fiaschi, Pedro; Frodin, David G. (Phytotaxa, 2014)
New combinations and lectotypes are here proposed for two Brazilian species of Dendropanax (Araliaceae): Dendropanax simplicifolius for Didymopanax simplicifolius from northern Mato Grosso Amazonian forests, and Dendropanax pruinosus for Gilibertia pruinosa, known only from gallery forests in the Chapada dos Veadeiros region. Both of these species are very poorly known and more collections will be required to achieve a better understanding of their morphological variability and circumscription.